Sustainability, Value, Performance and Risk in the Brazilian Capital Markets - Lameira, Valdir de Jesus; Ness Jr., Walter Lee; Quelhas, Osvaldo Luis Gonçalves; Pereira, Roberto Guimarães (Review of Business Management, 2013)
The study of the relationship between best practices in sustainability and better business management is one of the most relevant and current issues involving researchers and professionals related to this theme. For this survey, a representative sample of 205 Brazilian publicly traded companies, for the period between 2005 and 2009, was selected. A possible relationship between ranking in the Bovespa sustainability index, used as a proxy for sustainability best practices, and indicators of management quality of those companies was investigated. After applying a variety of econometrics models, it was possible to confirm that best sustainability practices are associated with higher performance, higher value and lower risk. Moreover, sustainability is associated to value, both directly and through mediated variables of performance and risk. Finally, market value, operating leverage, return on assets (ROA) and volatility are possible determinants of sustainability practices quality.